2010
DOI: 10.1007/s11604-010-0482-5
|View full text |Cite
|
Sign up to set email alerts
|

Segmental acquisition method for stationary objects in 18F-fluorodeoxyglucose positron emission tomography tests

Abstract: For stationary objects, the quality of images obtained by the segmental method is equivalent to that of images obtained conventionally by continuous acquisition. Moreover, under some conditions SIs provide better results than CIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The concentration of radioactivity in the background area was set to match that of the back muscles of 20 actual patients. 4 The spheres were filled with FDG solution so that the ratio of radioactivity concentration in the spheres to that of the background area was 8:1, in accordance with the MEMA NU-2 2018 standard. 8 The scattering phantom was filled with FDG solution with radioactivity of 66.0 MBq.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of radioactivity in the background area was set to match that of the back muscles of 20 actual patients. 4 The spheres were filled with FDG solution so that the ratio of radioactivity concentration in the spheres to that of the background area was 8:1, in accordance with the MEMA NU-2 2018 standard. 8 The scattering phantom was filled with FDG solution with radioactivity of 66.0 MBq.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study demonstrated that the segmental acquisition method using a Fourier rebinning (FORE) + ordered subsets expectation-maximization (OSEM) reconstruction algorithm could suppress the effects of body motion and improve the image quality of FDG PET, 4 but the effects of this reconstruction algorithm on image data obtained with a short acquisition time have not been well investigated yet. Therefore, we aimed to develop a reconstruction algorithm for a short acquisition time so that it can also be applied to dynamic studies and, by obtaining image data repeatedly with a short scan time, we can obtain PET images from image data that are not affected by body motion, even when body movements occur.…”
Section: Introductionmentioning
confidence: 99%